The social capital of a firm: are we focusing on the right facet? - Czakon, Wojciech; Lizak, Dariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
Social capital is a recognized concept in management literature. While its many components have been found to have an impact on a firm's competitive advantage, there is a literature gap concerning their relative importance. Our study tests 10 hypotheses referring to the social capital components' individual and collective impact on a firm's competitive advantage. The study was conducted in the Polish packaging industry. Our evidence confirms the positive relationship of structures, processes, norms and attitudes as social capital components to competitive advantage. We also find evidence that the relationships between social capital and competitive advantage is linear, contrary to the "paradox of embeddedness" hypothesis which suggests that social capital displays a non-linear relationship with performance
Argumenta Oeconomica, 2013, Nr 2 (31), s. 97-116
Keywords: social capital; structures; competitive advantage; embeddedness